PENGARUH PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT SIBOLGA SAMBAS - Azman Pasaribu; Nelly a sinaga; Jeniusman hutagalung (CV. ALIM'SPUBLISHING, 2025)
Writing this thesis aims to determine the effect of training and human resource development on employee performance at the Sibolga Sambas sub-district office. The problem encountered in this study is that there are employees who are not disciplined and lack experience in their work.The formulation of the problem in this study is what is the effect of training and human resource development on employee performance at the Sibolga Sambas sub-district office? Meanwhile, the purpose of this research is to find out whether there is an effect of training and human resource development on employee performance at the Sibolga Sambas sub-district office. The proposed hypothesis is that there is an effect of training and human resource development on employee performance at the Sibolga Sambas sub-district office. The population in this study were PNS and THL employees at the Sibolga Sambas sub-district office totaling 70 people. The data collection technique is done by distributing questionnaires. The data analysis technique used is quantitative analysis.It can be concluded that, Ha is accepted. For this reason, it is recommended that companies pay attention to HR training and development in order to improve employee performance. However, this application is not the only strategy that must be done, because there are many other strategies to improve employee performance which are not the author's study.